THE DEVELOPMENT OF THE TRAINING COURSE TO ENHANCE ENGAGEMENT LEADERSHIP FOR DRUG ABUSE PREVENTION OF POLICE NURSING STUDENTS - Krachangpho, Patcharee; Suthasinobon, Kittichai; Langka, Wilailak (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2023)
The purposes of this research were to develop and evaluate the training course to enhance engagement leadership for drug abuse prevention of police nursing students. The sample comprised 30 third-year police nursing students, academic year 2022. The research instruments were 1) the interview note with experts examining the components of leadership and training course, 2) the training course to enhance engagement leadership for drug abuse prevention of police nursing students, approved by 5 experts, with the content validity equaled to 1.00, and 3) the evaluation form of engagement leadership for drug abuse prevention in knowledge, skill, and characteristic aspects, approved by the 5 experts, with the Index of item objective congruence (IOC) at 1.00 and with Cronbach’s Alpha Coefficient at .82, .81, and .80, respectively. Quantitative data analysis was conducted by the calculation of percentage, mean, standard deviation, paired t-test, and content analysis was used for qualitative data. The results of the research showed that the training course to enhance engagement leadership for drug abuse prevention of police nursing students exhibited the suitability at the highest level (M = 4.98, SD = .05), and was capable of encouraging engagement leadership for drug abuse prevention of police nursing students in terms of knowledge, skills, and characteristics at the highest level (M = 4.90, SD = .22). Moreover, it was found that after having implemented the training course, the average score of engagement leadership for drug abuse prevention of police nursing students was higher than the average score before implementing the training course, with statistical significance at the level of .05.